THE EFFECT OF STORY PLAY THERAPY ON LANGUAGE DEVELOPMENT OF CHILDREN WITH MENTAL RETARDATION AT RELA SLB BHAKTI I GAMPING SLEMAN YOGYAKARTA - Tri Arini (UNEJ e-Proceeding, 2020)
Background: Retardation mental is child who has lack ability of adaptive behavior and intellectuals below average that appears during development process. The emergence of various developmental barriers in children with mental retardation is a phenomenon that needs to be further addressed so that the children with mental retardation can still live a good life and optimize the slightest their abilities, including increasing language skills. Purpose: To determine the effect of story play therapy on language development in children with mental retardation at SLB Rela Bhakti I Gamping Sleman Yogyakarta. Method: The type of research is Quasi-experimental with the design of "Pre-test Post-test with Control Group Design.". The result of examination data was analysed descriptively and analytically by using SPSS for windows version 16.0 with Paired Samples Test, for a significant level of 0.05. Results The results of the Paired Samples Test in the treatment group showed that the p value was = <0.001 (p <0.05) and the CI 95% was between -5.91 to -2.76 and it did not pass 0 (zero), statistically it shows that there was a significant difference in the mean language development of children before and after giving story play therapy. Whereas the control group showed that the p value = 0.49 (> 0.05) and 95% CI between -0.28 to 0.55 and exceeding 0 (zero). Therefore, there was no difference in the mean language development of children for before and after giving story play therapy. Conclusion: Story play therapy can improve language development in children with mental retardation at SLB Rela Bhakti I Gamping Sleman Yogyakarta Keywords: Story play therapy, mental retardation children